Association of Resident Duty Hour Restrictions, Level of Trainee, and Number of Available Residents with Mortality in the Neonatal Intensive Care Unit - Beltempo, Marc; Clement, Karin; Lacroix, Guy; Bélanger, Sylvie; Julien, Anne-Sophie; Piedboeuf, Bruno (American Journal of Perinatology, 2018)
Objective This article assesses the effect of reducing consecutive hours worked by residents from 24 to 16 hours on yearly total hours worked per resident in the neonatal intensive care unit (NICU) and evaluates the association of resident duty hour reform, level of trainee, and the number of residents present at admission with mortality in the NICU.Study Design This is a 6-year retrospective cohort study including all pediatric residents working in a Level 3 NICU (N = 185) and infants admitted to the NICU (N = 8,159). Adjusted odds ratios (aOR) were estimated for mortality with respect to Epoch (2008–2011 [24-hour shifts] versus 2011–2014 [16-hour shifts]), level of trainee, and the number of residents present at admission.Results The reduction in maximum consecutive hours worked was associated with a significant reduction of the median yearly total hours worked per resident in the NICU (381 hour vs. 276 hour, p < 0.01). Early mortality rate was 1.2% (50/4,107) before the resident duty hour reform and 0.8% (33/4,052) after the reform (aOR, 0.57; 95% confidence interval [CI], 0.33–0.98). Neither level of trainee (aOR, 1.22; 95% CI, 0.71–2.10; junior vs. senior) nor the number of residents present at admission (aOR, 2.08; 95% CI, 0.43–10.02, 5–8 residents vs. 0–2 residents) were associated with early mortality. Resident duty hour reform was not associated with hospital mortality (aOR, 0.73; 95% CI, 0.50–1.07; after vs. before resident duty hour reform).Conclusion Resident duty hour restrictions were associated with a reduction in the number of yearly hours worked by residents in the NICU as well as a significant decrease in adjusted odds of early mortality but not of hospital mortality in admitted neonates.
Keywords: infant; premature; workforce; resident education/training; morbidity/mortality